Pemphigus foliaceus in a sheep - Cavalcanti, Aline Antas Cordeiro; Campos, Ana Claudia; Moraes, Aline Guedes Mamede; Pessoa, Clarice Ricardo de Macêdo; Riet-Correa, Franklin; Melo, Marcia Almeida; Azevedo, Edisio Oliveira (Semina: Ciências Agrárias, 2019)
Pemphigus foliaceus (PF) is an autoimmune disease of the skin and is the most common form of pemphigus in domestic animals. This work reports a case of pemphigus foliaceus in a Santa Inês hair sheep. The ewe presented with multifocal bilateral crusted alopecic dermatitis affecting the chest, abdomen, and pelvic and thoracic limbs. Parakeratotic hyperkeratosis and acanthosis, in addition to subcorneal pustules, were observed histologically, and acantholytic cells and neutrophils were observed within the pustules. In the superficial and deep dermal tissues, there was intense eosinophilic infiltration and the presence of rare macrophages. These microscopic findings were characteristic of PF, and treatment with dexamethasone was ineffective. This disease is rare in sheep, and this is the first case report to be published in Brazil.